2015
DOI: 10.1186/s12864-015-1398-3
|View full text |Cite
|
Sign up to set email alerts
|

Hsf and Hsp gene families in Populus: genome-wide identification, organization and correlated expression during development and in stress responses

Abstract: BackgroundHeat shock proteins (Hsps) are molecular chaperones that are involved in many normal cellular processes and stress responses, and heat shock factors (Hsfs) are the transcriptional activators of Hsps. Hsfs and Hsps are widely coordinated in various biological processes. Although the roles of Hsfs and Hsps in stress responses have been well characterized in Arabidopsis, their roles in perennial woody species undergoing various environmental stresses remain unclear.ResultsHere, a comprehensive identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
104
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(119 citation statements)
references
References 69 publications
11
104
1
1
Order By: Relevance
“…Metal pollution is a tremendous problem faced by the local government in southern Jiangxi Province.Molybdenum and cadmium are the main pollutants in the tailings in the process of mining, which pose hazardously threats to animals and public health. Heat shock proteins are molecular chaperones that are involved in many normal cellular processes and stress responses [16]. HSPs represent a highly conserved class of cytoprotective proteins specifically induced at the cellular level in response to one of several environmental stressors and protect cells against environmental stress [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Metal pollution is a tremendous problem faced by the local government in southern Jiangxi Province.Molybdenum and cadmium are the main pollutants in the tailings in the process of mining, which pose hazardously threats to animals and public health. Heat shock proteins are molecular chaperones that are involved in many normal cellular processes and stress responses [16]. HSPs represent a highly conserved class of cytoprotective proteins specifically induced at the cellular level in response to one of several environmental stressors and protect cells against environmental stress [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…They were mainly found in the inner parts of the cell, membranes, and organelles. When other studies in the literature were examined, it was found that Hsp families were mostly located in intracellular parts in eucalyptus (Çelik Altunoğlu, 2016) and poplar (Zhang et al, 2015;Yer et al, 2016;Yer et al, 2018). The results for watermelon Hsp proteins have parallels with the results of these studies.…”
Section: Discussionmentioning
confidence: 63%
“…In the ClasHsp, ClaHsp40, and ClaHsp70 families, exonsintrons were approximately equal, while very few introns were detected in ClaHsp100 and no introns were observed in the ClaHsp60 and ClaHsp90 families. When the other studies were examined, it was seen that the exon structure predominated in the sHsp, Hsp70, and Hsp100 genes of the Hsp families in the A. thaliana genome (Zhang et al, 2015). When the Hsp70 family in the eucalyptus genome was examined, it was found that there were an approximately equal number of exon-intron structures as in the watermelon Hsp70 family (Çelik Altunoğlu, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…With the complement of genome DNA sequencing project, Hsf family members had been identified in more than 20 plant species at genome-wide scale [7], including Oryza sativa L. [8], Pyrus bretschneideri [13], Sorghum bicolor [14] and Populus [15]. The maximum of Hsf genes among monocots is 56 which was identified in wheat, while the maximum of Hsf genes among dicots were found in soybean [4].…”
Section: Introductionmentioning
confidence: 99%